Pore structure characterization of coal by synchrotron radiation nano-CT. (1st March 2018) - Zhao, Yixin; Sun, Yingfeng; Liu, Shimin; Chen, Zhongwei; Yuan, Liang
Highlights: Synchrotron radiation nano-CT was adopted for the pore structure characterization of coal. Between-class Variance Maximisation (BCVM) algorithm was applied to segment nano-CT images. Pores are partitioned and statistics of pore and throat were conducted. Nanopore structure-based computational fluid dynamics (CFD) simulation was explored. Abstract: For the significant impact of pore structure on gas storage and transport in coal seams, research on coal pore structure characterization has been a hotspot. Benefited from the high spatial resolution synchrotron-based nano-CT instrument, pore structure characterization of coal is investigated in nano scale. Image alignment and 3D reconstruction were completed at the platform designed by National Synchrotron Radiation Laboratory and Chinese Academy of Sciences. The segmentation of the unimodal grey-scale value histograms is solved by Between-class Variance Maximisation (BCVM) algorithm and the nano-CT images are segmented into three components, pore, organic components and mineral components. Based on the voxel number, components fraction is computed. Pore size distribution (PSD) presents bimodality. Pores with equivalent radius less than 60 nm account for 84% of the total pore number. Throats with equivalent radius less than 60 nm account for 89% of the total throat number. Throats with length less than 100 nm account for 58% of the total throat number and throats with length less than 400 nm account for 84% of the total throat number. Pore number decreases with the increase of coordination number. There are over 50% of pores without coordination pore and pore connectivity was analysed. Nanopore structure-based computational fluid dynamics (CFD) simulation was explored. The permeability in three coordinate axes directions presents anisotropy.